Análise de esforços em estruturas aporticadas com fundações em estacas - Diniz, Roberto Antônio da Costa (1972)
The present work has as its main goal determination of loads acting on bridge frames supported by piles or bored piles under the condition of horizontal loading. Theories on laterally loaded piles are discussed and an application of the stiffness method to the analysis of plane frames by means of digital computers is shown. ln the last Chapter a few practical examples are solved, and graphs for the determination of the maximum bending moment of piles are presented for two hypothesis of the soil reaction modulus: constant or varying linearly with depth.